Biomass-derived fiber materials for biomedical applications - Li, Daixiu; Wang, Yilin; Huang, Wenhua; Gong, Haihuan (Frontiers in Materials, 2023)
With the development of sustainable materials, biomass-derived fiber materials have attracted significant research interest because of their excellent performance, cost-effectiveness, and environmental friendliness. Following their extensive use in biomedical applications, biomass-derived fiber materials are now increasingly used in antibacterial skin-wound dressings, bone tissue engineering, drug delivery, etc. However, their practical medical applications are still in their infancy, requiring some reference and strategic directions for the future clinical applications of biomaterials in medicine and cross-discipline use, some of which are provided in this review. The sources and characteristics of the different biomass-derived fibers are introduced briefly, encompassing polysaccharide fiber and protein fiber’s two categories. Then, we summarize the common applications of biomass and its derived fibers in the medical field in recent years. Finally, we discuss the application and advantages of three-dimensional printing technology combined with biomass-derived materials in modern medicine for a better understanding of the practical applications of biomass-derived fiber materials.